Pengaruh Penerapan Strategi Genius Learning terhadap Kemampuan Berpikir Kreatif Peserta Didik Kelas X IPA SMA - Bepi Patrira; Ajo Dian Yusandika; Henny Wulandary (U-Teach: Journal Education of Young Physics Teacher, 2020)
The teacher has never applied and measured the creative thinking skills of class X students. However, after the researchers made observations on the creative thinking skills of students in this school, the results were in the low category. The purpose of this study was to see the effect of the application of the genius learning strategy on the creative thinking skills of students of class X majoring in science in physics learning on the subject of linear motion at SMAN 1 Pulaupanggung. The research method used in this research was quasy experiment. The design used in this study was the nonequivalent control group design. A total of 64 students of class X SMAN 1 Pulaupanggung consisting of 2 classes were selected as the research sample using purposive sampling technique. The data collection technique used was a test instrument in the form of 9 essay questions. Then, the data were processed using the normality test and homogeneity test which were then analyzed using the average difference test (t-test). The application of the genius learning strategy has an effect on improving the creative thinking skills of students on the subject of straight motion at SMAN 1 Pulaupanggung.